Using priority effects to manipulate competitive relationships in restoration. (26th May 2016) - Young, Truman P.; Stuble, Katharine L.; Balachowski, Jennifer A.; Werner, Chhaya M.
Abstract: Restoration success is often hampered by the failure of less dominant competitors to establish. An emerging literature on priority effects suggests the manipulation of community assembly as a useful technique to help overcome these difficulties by altering competitive relationships. We present data from a set of four priority experiments, carried out at each of three sites in restoration settings in California grasslands. These data, combined with patterns summarized from the literature, indicate that both short‐term priority (1–3 weeks) and long‐term priority (1 year) can profoundly shift interspecific relationships and benefit otherwise subordinate plant species, but that these effects are sometimes transitory, asymmetric, and contingent on environmental conditions and species composition. Restoration interventions that can produce priority effects include staggered planting times, weed control, seed pre‐germination, plug planting, and spatial aggregation. Such interventions are likely to be at least initially effective, but their strength and persistence can differ considerably across systems in space and time. Further research may help identify the conditions that maximize the strength and persistence of priority effects in restoration settings.